The Use of Defatted Tenebrio molitor Larvae Meal as a Main Protein Source Is Supported in European Sea Bass (Dicentrarchus labrax) by Data on Growth Performance, Lipid Metabolism, and Flesh Quality - Basto, Ana; Calduch-Giner, Josep; Oliveira, Beatriz; Petit, Lisa; Sá, Tiago; Maia, Margarida R. G.; Fonseca, Susana C.; Matos, Elisabete; Pérez-Sánchez, Jaume; Valente, Luisa M. P. (Frontiers in Physiology, 2021)
Objective: This study aims to determine the maximal inclusion level of defatted (d-) Tenebrio molitor larvae meal (TM) able to replace dietary FM without compromising growth performance, general metabolism, and flesh quality traits in European sea bass, and to evaluate the major underlying physiological mechanisms. Methods: Fish (58 ± 1 g) were fed with diets containing increasing levels of dTM: 0, 40, 80 and 100% (CTRL, TM40, TM80 and TM100, respectively) to replace FM. After 10 weeks of feeding, the growth performance, nutrient and energy balance, intestinal integrity, plasma metabolites and the expression of genes related to growth and nutrient metabolism, in liver and muscle, were determined. The fatty acids (FAs) profile, textural properties and colour were also evaluated in muscle. Results: Protein and lipids digestibility remained unaltered up to 80% dTM inclusion. Growth performance parameters were similar among dietary treatments. The dTM inclusion increased the hepatosomatic index in TM100. Muscle eicosapentaenoic acid, docosahexaenoic acid and n-3 long-chain polyunsaturated FAs levels were maintained up to 80% dTM inclusion, but total cholesterol and non-esterified FAs increased with dietary dTM inclusion. In liver, the expression of elongation of very long-chain FAs protein 6 (elovl6) and FAs desaturase 2 (fads2) did not change in TM40 and TM80, but elovl6 decreased whilst fads2 increased in TM100 when compared to CTRL. The expression of cholesterol 7 alpha-monooxygenase (cyp7a1) decreased with dietary dTM inclusion. In muscle, the expression of myoblast determination protein-2 (myod2) decreased in fish fed TM80 and TM100. Conclusion: It is feasible to substitute dietary FM by dTM up to 80% in European sea bass without detrimental effects on nutrient digestibility, growth performance and associated genetic pathways, whilst assuring fillet nutritional value for human consumption.